The Role of Social Media Usage on Conspicuous Online Consumption among Millennial Consumers - Irma Lidya A Sastra; Siti Halida Zia; Muhammad Fadel Asyahid; Nur Damayanti (Journal of Economics, Business, and Accountancy Ventura, 2023)
The ubiquity and maturation of the Internet and social media have given rise to social phenomena that impact consumer behavior, particularly in the realm of conspicuous online consumption. This study builds upon prior research by examining the factors influencing conspicuous online consumption among millennials in Jakarta who engage with social media platforms like YouTube and Instagram. The research methodology involved an online survey administered to 400 respondents, with data subsequently analyzed through a structural equation model, utilizing SmartPLS 4.0 software. The results illuminate a noteworthy positive correlation between the four variables studied. Moreover, they indicate that feelings of envy and materialism serve as mediating factors in the relationship between social media usage and conspicuous online consumption. In sum, this study offers valuable insights into the comprehension of conspicuous online consumption and its associated variables, bearing significance for both theory and practical applications. However, it's important to note certain limitations, such as the exclusive focus on the millennial cohort in Jakarta and the fact that the selected social media platforms were not explicitly linked to the mediating variables. Future research endeavors should explore the attitudes of other cohorts toward conspicuous online consumption among social media users.